The fulcrum axis: an accurate measure of glenoid version on radiographs and computed tomography. (April 2019) - Mutch, Jennifer; Sidler, Martin; Sidler-Maier, Claudia; Axelrod, Terry; Nam, Diane
Background: Proper glenoid position in total shoulder arthroplasty (TSA) is important. However, traditional glenoid version (GV) measurements overestimate retroversion on radiographs (XR) and computed tomography (CT). The fulcrum axis (FA) uses palpable surface landmarks and may be useful as an intra-operative guide. Also, the FA has not yet been validated on XR or CT in an arthritic population. Methods: Four observers measured FA and GV on the XR, CT and three-dimensional CT (3DCT) of 40 patients who underwent TSA at a single institution from 2009 to 2015. Reliability and accuracy of FA and GV were calculated for XR and CT, using 3DCT as the gold standard. Results: The mean FA and GV were 7.768° and 18.910° on XR; 6.23° and 12.920° on CT; and 8.100° and 7.740° on 3DCT, respectively. FA and GV were significantly different for XR and CT ( p  < 0.001) but not for 3DCT ( p  = 0.725). The inter-rater reliability, intra-rater reliability and accuracy of FA were not significantly different from GV and were 0.929 to 0.948, 0.779 to 0.974 and 0.674 to 0.705, respectively. However, the absolute difference of FA was closer to the gold standard (3DCT) than GV for XR (0.330° versus 11.172°) and CT (1.871° versus 5.178°) ( p  < 0.001). Conclusions: FA showed comparable reliability and accuracy to GV. However, FA more accurately reflected the gold standard.